THE EFFECT OF MSME’s FINANCIAL STATEMENTS QUALITY TO BANKING CREDIT ACCESSIBILITY - Rizka Rahmah Asaidah; Khairina Nur Izzaty (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
The purpose of this study is examine the extent to which SMEs actors prepare annual reports and how the level of loan access that can be received by SMEs with quality annual reports. This study uses primary data obtained from question with respondents of 50 SMEs at Rumah Kreatif BUMN Bank BRI Cabang Pandanaran Semarang. The analysis technique used multiple linier regression. The results of this study indicate that the quality of SMEs annual report and loan term has no effect on the bank loans access, this is due to the low SMEs annual reports that cause banks to still doubt the trust related to their annual report. While the size of the business, length of business, and loan collaterals have a positive effect on the amount of bank loans access.